Validity of the scoring system technology for detecting points in archery - Humaid, H.; Pelana, R.; Chia-Smith, W.; Winata, B.; Yulianti, E.; Wattimena, F. Y.; Artono, E. (Journal of Physical Education and Sport, 2021)
In amateur and junior level archery competition, judges and trainers manually determine the points earned by archers by either using binoculars or by approaching the target board to observe and validate the position of the arrow. Therefore, the aim of this study is to develop and test the validity and reliability of the scoring system technology (SST) for detecting points automatically. The SST was manufactured by combining several components such as aluminum, microcontroller, light-emitting diode (LED) display monitor, and power supply. Furthermore, after its manufacture, the experimental aspect which involved the archers of various skill levels, which consisted professional (n=5) and amateurs (n=5). They were instructed to shoot three arrows from a distance of 30-meter at the Fédération Internationale de Tir à l'Arc (FITA) target face equipped with SST. The performances were directly reported to the archers through the LED panel. Simultaneously two FITA certified judges observed the shots behind the archers and recorded their performances. Descriptive statistics and ANOVA examined the scores collected from SST and judges observations. The statistical analysis results which were obtained using the one-way ANOVA showed that there was no significant difference (p = 1.0) between the points generated by the SST and the Judges. The findings suggest that that SST could provide a valid scoring system for archery competitions.